Sistem Pendukung Keputusan Eligible Seleksi Nasional Berdasarkan Prestasi (SNBP) Menggunakan Metode Additive Ratio Assessment (ARAS): Studi Kasus: SMAN 8 Surabaya - Rhiziqo Adjie Syahputra; Henni Endah Wahanani; Budi Mukhamad Mulyo (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The selection process for students eligible for the National Selection Based on Achievement (SNBP) requires objective and structured assessment because it involves various academic and non-academic criteria. This study aims to develop a Decision Support System (DSS) to determine the ranking of SNBP eligible students at SMAN 8 Surabaya using the Additive Ratio Assessment (ARAS) method. The ARAS method is used to evaluate student alternatives based on their report card scores for semesters 1-5, academic ability tests (TKA), academic achievements, non-academic achievements, discipline, organizational activity, and attendance through a normalization process to obtain relative Ki values. The results of the study show that the system is capable of producing objective student rankings with relative utility values (Ki) ranging from 95.15 to 89.38, where the highest value indicates the best alternative from all alternatives. The application of ARAS-based DSS can improve the efficiency, transparency, and consistency of the SNBP student selection process.